Peningkatan Pemahaman Mengenai Konsep Keselamatan Kepada Naposo GKPA Janji Angkola - Phiniel Josia Hutabarat; Trivena Br Nadeak; Jeri Hesekiel Lumbantobing; Jefri Ade Nasuton; Mely Triani Sihombing (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2024)
This article discusses efforts to increase understanding of the concept of salvation for the Naposo of the Angkola Protestant Christian Church (GKPA) Angkola Promise through holding field seminars. The doctrine of salvation is the core teaching in Christianity which includes the condition of humans who have fallen into sin, the gift of salvation through Jesus Christ, and the process of repentance and faith. The research methods used include an initial survey, development of seminar materials, implementation of interactive activities, and post-seminar evaluation through questionnaires and interviews. Results showed significant improvement in Naposo's understanding of safety, with active participation in activities and positive response to interactive teaching methods. Participant feedback indicated a desire for continued activities to strengthen faith and application of salvation teachings in daily life. This article emphasizes the importance of a comprehensive and relevant approach in teaching the doctrine of salvation, as well as its impact in forming a generation of young people who are strong in the faith and witnesses of Christ in society.